PENGARUH STRATEGI PEMBELAJARAN HIGHER ORDER THINKING TERHADAP KEMAMPUAN MENULIS TEKS ANEKDOT SISWA KELAS X SMA NEGERI 1 TELUKDALAM - ZALUKHU, MERRI CHRISTINA (JURNAL EDUCATION AND DEVELOPMENT, 2018)
A persons language skills are related to his ability to think. The ability to write of someone is determined by how he thinks then takes it out through written language. Therefore, the ability to think must also be trained early on well. In the learning process, students are less encouraged to develope their thinking skills. Higher Order Thinking (HOT) learning strategies are applied to see the effect on the ability to write anecdotal texts. This research was carried out using quasi-experimental method with static group comparison research design model. The population in this study were all class X students of SMA Negeri 1 Telukdalam, South Nias in the 2017/2018 learning year totaling 252 people. The sampling technique was carried out purposively (purposive sampling). The number of samples in this study was 66 people. Class X IPA Anggrek is a control class (31 people) and Class X IPA Dahlia is an experimental class (35 people). This research instrument is an essay-shaped test. The results showed that based on the t test performed, t0> t table, namely 1.88> 1.669. Thus H0 (null hypothesis) is rejected and Ha (alternative hypothesis) is accepted. It can be concluded that the application of HOT (Higher Order Thinking) learning strategies has a positive effect on the learning outcomes of class X SMA Negeri 1 Telukdalam T.A. 2017/2018.